A CPW-Fed Monopole Antenna with Double Rectangular Rings and Vertical Slots in the Ground Plane for WLAN/WiMAX Applications - Sangjin Jo; Hyunjin Choi; Jaehyuk Lim; Beomsoo Shin; Sangyeol Oh; Jaehoon Lee (International Journal of Antennas and Propagation)
A compact triple-band monopole antenna consisting of double rectangular rings and vertical slots cut into the ground is proposed for WLAN and WiMAX operations. The antenna has a compact size of 27.1 × 38.8 × 1.6 mm3, with simulated and measured impedance bandwidths of 2.37~2.81, 3.21~3.82, and 4.61~6.34 GHz with a reflection coefficient of less than −10 dB. The antenna also exhibits an almost omnidirectional radiation pattern and stable gain levels in the triple bands. The characteristics of the proposed antenna have been investigated using the numerical simulations and experiments.